2014
DOI: 10.1155/2014/239621
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Polyamine Metabolism and Abiotic Stress Tolerance

Abstract: Global warming is an alarming problem in agriculture and its effect on yield loss has been estimated to be five per cent for every degree centigrade rise in temperature. Plants exhibit multiple mechanisms like optimizing signaling pathway, involvement of secondary messengers, production of biomolecules specifically in response to stress, modulation of various metabolic networks in accordance with stress, and so forth, in order to overcome abiotic stress factors. Many structural genes and networks of pathway we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 77 publications
2
40
0
1
Order By: Relevance
“…Polyamines (PAs), small bioactive molecules with two or more amino groups, have been found widely in microbes, animals, and plants. There are three major PAs in plants, including putrescine (Put), spermidine (Spd), and spermine (Spm), with a sequential biosynthetic pathway (Put → Spd → Spm) . Catabolism of PAs mediated by polyamine oxidase (PAO) has been considered to be an important biosynthetic pathway of H 2 O 2 in plants .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyamines (PAs), small bioactive molecules with two or more amino groups, have been found widely in microbes, animals, and plants. There are three major PAs in plants, including putrescine (Put), spermidine (Spd), and spermine (Spm), with a sequential biosynthetic pathway (Put → Spd → Spm) . Catabolism of PAs mediated by polyamine oxidase (PAO) has been considered to be an important biosynthetic pathway of H 2 O 2 in plants .…”
Section: Introductionmentioning
confidence: 99%
“…There are three major PAs in plants, including putrescine (Put), spermidine (Spd), and spermine (Spm), with a sequential biosynthetic pathway (Put → Spd → Spm) . Catabolism of PAs mediated by polyamine oxidase (PAO) has been considered to be an important biosynthetic pathway of H 2 O 2 in plants . PAOs prefer to catalyze the deamination metabolism of PAs with more than two amino groups, such as Spd and Spm, along with the generation of H 2 O 2 as a by‐product .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naturally occurring polyamines-spermine, spermidine, cadaverine and putrescine, are widespread in the nature and play a crucial role in processes of cell growth, differentiation, development and death [1][2][3]. Although their biochemistry and physiologic role is not well understood it was shown that they are implicated in growth and development of neoplastic cells [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines are the aliphatic nitrogen (natural organic polycation) compounds found in a wide variety of living organisms including plants and animals with a low molecule weight and a positive charge in physiological pH (Roychoudhury et al, 2011). Polyamines are effective in the plant adaptation against various environmental stresses: salinity, hyperosmosis, high temperature, low temperature, drought, pH stress, hypoxia, environmental pollutants (Rangan et al, 2014). The studies conducted demonstrated that spermidine (spd) is participating in the regulation of plant responses to diverse abiotic stresses like drought or osmotic stress, salinity, heat and chilling through direct binding to membrane phospholipids, osmotic adjustment, scavenging of free radicals and maintaining a cation-anion balance (Kusano et al, 2008).…”
Section: Introductionmentioning
confidence: 99%